Investigating the Antifungal Effects of Spirocyclopropane Oxindoles Derivatives Against Aspergillus Species - Amirreza Ardebilifard; Akbar Hoseinnejad; Jalal Jafarzade; Nava Hajizadeh Jouybari; Aida Rajabnia Baboli; Asieh Khalilpour; Firoozeh Kermani; Aryan Yousefifard; Mojtaba Taghizadeh Armaki (Research in Molecular Medicine)
Background: Given the increasing resistance of Aspergillus spp. to azoles, finding effective new compounds, such as the spirocyclopropane oxindoles (4a-4b-4c) derivatives, seems necessary. The present study aimed to evaluate the antifungal activity of spirocyclopropane oxindoles (4a-4b-4c) derivatives against Aspergillus spp.